Variation in Population Vulnerability to Heat Wave in Western Australia - Xiao, Jianguo; Spicer, Tony; Jian, Le; Yun, Grace Yajuan; Shao, Changying; Nairn, John; Fawcett, Robert J. B.; Robertson, Andrew; Weeramanthri, Tarun Stephen (Frontiers in Public Health, 2017)
Heatwaves have killed more people in Australia than all other natural hazards combined. Climate change is expected to increase the frequency, duration, and intensity of heatwaves and lead to a doubling of heat-related deaths over the next 40 years. Despite being a significant public health issue, heatwaves do not attract the same level of attention from researchers, policy makers and emergency management agencies compared to other natural hazards. The purpose of the study was to identify risk factors that might lead to population vulnerability to heatwave in Western Australia. Heatwave vulnerability and resilience among the population of the State of Western Australia (WA) were investigated by using time series analysis. The health impacts of heatwaves were assessed by comparing the associations between hospital emergency department (ED) presentations, hospital admissions and mortality data, and intensities of heatwave. Risk factors including age, gender, socio-economic status (SES), remoteness, and geographical locations were examined to determine whether certain population groups were more at risk of adverse health impacts due to extreme heat. We found that hospital admissions due to heat-related conditions and kidney diseases, and overall ED attendances, were sensitive indicators of heatwave. Children aged 14 years or less and those aged 60 years or over were identified as the most vulnerable populations to heatwaves as shown in ED attendance data. Females had more ED attendances and hospital admissions due to kidney diseases; while males had more heat-related hospital admissions than females. There were significant dose-response relationships between heatwave intensity and SES, remoteness and health service usage. The more disadvantaged and remotely located the population, the higher the health service usage during heatwaves. Our study also found that some population groups and locations were resilient to extreme heat. We produced a mapping tool, which indicated geographic areas throughout Western Australia with various vulnerability and resilience levels to heatwave. The findings from this study will allow local government, community service organisations, and agencies in health, housing and education to better identify and understand the degree of vulnerability to heatwave throughout the state, better target preparatory strategies, and allocate limited resources to those most in need.